Transforming healthcare service delivery at a selected public hospital through appreciative inquiry - Mayeza, C. A.; Maluka, H. R. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
South African healthcare system is currently faced with challenges of service delivery that requires effective change management programmes. The South African government adopted Primary Healthcare (PHC) approach to deliver District Healthcare System (DHS), as a vehicle for the delivery of PHC. This also included the adoption of People First (Batho Pele) principles and "Batho Pele" strategy, in delivering healthcare services to the community from the hospital and its surrounding clinics. It is important to note that even during times of transformation, there could be lessons learned from the past, which could be valuable to be used in the future. The objective of the study was to obtain valuable information relating to past successes and strengths from senior employees, which could be used in driving transformation at a selected hospital. The study adopted a qualitative research design in the form of an appreciative inquiry, by asking pertinent questions about previous successes and strengths. In-depth interviews were conducted on 17 hospital senior employees in KwaZulu- Natal. Thematic analysis was adopted to analyse the data, whereby themes were created to group similar data. The interviewees identified the following as successes that the hospitals could promote: open communication channels (87%); provision of optimum healthcare to all (76%); empowerment of health workers (59%); conducting health awareness campaigns (47%); engaging workers in decision making (53%) and; promoting of team spirit (53%). The study used appreciative enquiry (AI) as an organisational development (OD) intervention method in change management programmes, and ascertaining valuable successes that are being valued by senior employees in the workplace. The study could contribute in designing change management programmes in the health sector. Appreciative Inquiry is one of the OD strategies that could be used to reduce resistance to change to healthcare reform programmes.
Journal article published in the 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Appreciative inquiry; Human resource management; Primary healthcare; Service delivery; Transformation; Health facilities; Primary health care -- South Africa; Social change